Profitability Ratio Analysis to Measure the Financial Performance of Food and Beverage Companies for the Period of 2020 – 2023 - Ramdhan, Anggal Noor; Yulianti, Nur Afni; Parlina, Nurhana Dhea (IJEBD (International Journal of Entrepreneurship and Business Development), 2025)
Objective: This study aims to evaluate the financial performance of companies in the food and beverage sector during the period 2020–2023 by analyzing the profitability ratio. Design/Methodology/Approach: This study applies a Descriptive Quantitative method. The study population included nine companies, while sample selection was conducted using purposive sampling techniques based on specific criteria. Data is obtained from financial statements available on www.idx.co.id website. Findings: Providing guidelines for companies in improving financial performance through profitability analysis Limitations/ Implications of the study: This study reinforces the theory that financial ratios, especially profitability ratios, play a role as the main indicator in assessing a company's financial stability and performance. In addition, this study also enriches academic insights on various factors that affect profitability in the food and beverage industry sector. Practical Implications: Can use the results of profitability ratio analysis to assess operational efficiency and determine profit increase strategies. Originality/ Value: This paper is original Paper Type: Research Paper